Conceptualizing Suicide Prevention in Firefighters Through the lens of the Interpersonal-Psychological Theory of Suicide: A Narrative Review. Issue 1 (2nd January 2022) - Henderson, Elizabeth
Abstract: Suicide is the 10th leading cause of death in the United States and is a significant public health problem. Suicide has also become a major concern among career American firefighters with rates for suicidal ideation and attempts in firefighters two to three times higher than rates in the general population. Firefighter suicide and mental health are major issues facing fire service leaders, mental health professionals, and most recently suicide experts. Despite an increased focus on understanding suicide in the fire service, there is little empirical evidence on the effectiveness of prevention in this population. The juxtaposition of elevated suicide rates with a dearth of empirical prevention data specific to firefighters warrants new approaches and conceptualizations of suicide prevention in this population. Grounded in the framework of the interpersonal-psychological theory of suicide (IPTS), this narrative review integrates select relevant firefighter specific suicide risk/protective factors and multi-level intervention/prevention literature to provide a structured approach to identifying current suicide intervention/prevention efforts with promising transportability to firefighters. Several recommendations for future intervention research specific to firefighters are also proposed.